Ecological causality of the central serous chorioretinopathy incidence in the Sumy region (Ukrainian Journal of Ophthalmology, 2026)
Background. Studying anthropoecological factors is required to specify risk factors and predictors of central serous chorioretinopathy (CSCR).Purpose. To analyze a level of atmospheric air pollution by Cr6+ and to assess its influence on the incidence of central serous chorioretinopathy among adult population of the Sumy region.Material and Methods. Data on registration of patients for CSCR treatment (according to ICD-10: Н35.7) from 2005 to 2017 were analyzed. The data were obtained in Statistical Department of Sumy Regional Clinical Hospital. Official information data on air pollution by Cr6+ emission at PJSC Sumy NPO were studied.Results. For the entire period of observation, the CSCR incidence in the Sumy region shows a clear tendency to increase. The correlation analysis confirmed the fact that CSCR is determined by Cr6+ emission in the atmospheric air and showed a direct (correlation coefficient r = 0.85) significant (p = 0.0007) relationship (Fig. 3) between the CSCR incidence rate and the levels of Cr6+ emission in the atmosphere.Conclusion. Cr6+ was found to have an indirect and induced effect on the CSCR incidence  in the Sumy region.
Keywords: central serous chorioretinopathy; chrome; ecological factor; correlation analysis